2011
DOI: 10.1093/humrep/der351
|View full text |Cite
|
Sign up to set email alerts
|

Hidden mosaicism in patients with Klinefelter's syndrome: implications for genetic reproductive counselling

Abstract: Diagnosis of homogeneous KS based on lymphocyte karyotyping should be contrasted in other tissues. Mucosa cells could help to better approximate the degree of germ cell mosaicism. Our results indicate that 47,XXY germ cells are not meiotically competent. Increased post-reductional aneuploidy rate is related to meiotic errors in 46,XY cells. Appropriate genetic counselling is recommended in KS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…These data could also explain why mosaic Klinefelter (mos 47,XXY/46XY) patients display oligospermia or cryptozoospermia more frequently. Given that more 46,XY spermatocytes are expected to be present in the testis, they would tend to achieve spermatogenesis, as confirmed recently for 5 mosaic KS patients (Garcia‐Quevedo et al, 2011) and observed for mosaic 45,X/46,XY patients (Giltay et al, 2000).…”
Section: Discussionsupporting
confidence: 60%
“…These data could also explain why mosaic Klinefelter (mos 47,XXY/46XY) patients display oligospermia or cryptozoospermia more frequently. Given that more 46,XY spermatocytes are expected to be present in the testis, they would tend to achieve spermatogenesis, as confirmed recently for 5 mosaic KS patients (Garcia‐Quevedo et al, 2011) and observed for mosaic 45,X/46,XY patients (Giltay et al, 2000).…”
Section: Discussionsupporting
confidence: 60%
“…Each sample was submitted for direct DNA sequencing and underwent an AciI restriction enzyme assay that selectively cuts CACNA1C-wild type (WT). The lymphocytederived gDNA was assessed for mutant and WT copy numbers, using a method previously described by Etheridge et al, 8 to quantify the degree of mosaicism present in the mother.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, mosaicism also contributes to the inheritance of other multisystem disorders, such as Klinefelter' s syndrome. 8 With such a wide variety of phenotypic manifestations in TS1, somatic and germline mosaicism provides limitless possibilities for presenting and concealing TS1-causative mutations.…”
mentioning
confidence: 99%
“…However, a number of factors complicate the use of human SCA syndromes as a model for examination of sex chromosome gene-dosage effects, including background genetic and environmental diversity, karyotypic mosaicism (Wolff et al 2010; Garcia-Quevedo et al 2011), and X chromosome parent of origin (Lepage et al 2013). These considerations make murine SCA models an attractive complement to the study of SCA in humans.…”
Section: Introductionmentioning
confidence: 99%